TRANSFORMATION OF RELIGIOUS VALUES: DIMENSIONS OF RELIGIOUS STUDIES AND SOCIOLOGY - Віта Титаренко; Людмила Филипович (Cхід, 2021)
The article is devoted to rethinking methodological approaches in understanding of religion as a value by religious studies. A critical attitude to the previous experience of interpreting a religious phenomenon allows us to perceive religion as a value equal with other types of human self-awareness. This is prompted by the very status of religion in the modern world, which is changing under the influence of globalization and secularization. One of the trends of these processes is the departure from the restrictions of “sectarianism” and “nationalism” in religion to the expansion of the boundaries of understanding spirituality as a universal religious value. The article determines the value of religion in its ontological status, its existentiality, vitality, epistemological meaning, praxeological questionability, in eschatological perspective and hierarchical priority of spirituality, goodness and humanity. Based on this understanding of religion, the authors explicate it in the system of religious values that are implemented in the daily lives of adherents of a particular religion and entire society. The article presents materials of sociological surveys of both international, all-Ukrainian and local levels. The comparative analysis of the received results allows to draw a conclusion about universalization of religious values, to define features of youth perception of religion as a value.